The Libro de los Buenos Proverbios : A Critical Edition - Ḥunayn ibn Isḥāq al-ʻIbādī, 809?-873 (Book collections on Project MUSE., 1970)
The libro de los buenos proverbios, a key work in the medieval didactic tradition, is presented here for the first time in a western translation. The proverbs were assembled by the great ninth-century physician, translator, and author, Hunain ibn Ishaq. Harlan G. Sturm provides an excellent introduction to his translation of the Buenos Proverbios which deals with the book's role in medieval proverbial literature and with the life and significance of Hunain ibn Ishaq, whose influence in his own period was significant. Hunain accurately translated the scientific works of the ancients and contr.